Integrating network pharmacology and experimental validation to reveal the anti-growth mechanism of panaxadiol against glioblastoma via calcium signaling - Qiu, Guobin; Wu, Zhiyong; Yang, Dunhui; Zhou, Luqiu (Frontiers in Molecular Biosciences, 2025)
Glioblastoma (GBM) is a highly aggressive brain tumor and is relatively common among malignant brain tumors in adults. Its rapid proliferation and significant invasiveness make its treatment one of the major challenges in brain tumor research. Panaxadiol, a compound extracted from ginseng roots, has been found to have significant therapeutic effects on various types of tumors. Nonetheless, the precise function and underlying mechanisms of this factor in GBM have yet to be thoroughly investigated. In the current study, we employed network pharmacology to explore the potential therapeutic interactions of Panaxadiol within the framework of GBM. Subsequently, we confirmed its efficacy via biological experiments aimed at elucidating the mechanisms through which it exerts its anti-GBM effects. We collected relevant targets of Panaxadiol and differential genes of GBM from multiple databases. The network pharmacology analysis revealed 66 potential targets of Panaxadiol in the context of GBM. Enrichment analysis indicated that these targets might function through several key signaling pathways, including the calcium, cAMP, and cGMP-PKG signaling pathways. Therefore, Panaxadiol may exert its effects by regulating calcium ions. Further, In our study, we employed the MOCDE and CytoHubba plugins within the Cytoscape framework to identify seven hub genes, including GRIA2, GRIN1, GRIN2B, GRM1, GRM5, HTR1A, and HTR2A, and validated their binding capabilities with Panaxadiol through molecular docking. Furthermore, we conducted experiments in vitro and in vivo experiments, which encompassed CCK-8, colony formation, flow cytometry apoptosis, intracellular calcium ion measurement, and xenograft tumor experiments utilizing nude mice, to validate the function of Panaxadiol in suppressing the growth of GBM via the modulation of calcium ion levels. This study not only revealed the anti-GBM mechanisms of Panaxadiol through network pharmacology but also validated its inhibitory effects on GBM via calcium ion release through in vitro and in vivo experiments.